Pengaruh Bermain Game Mobile Legends Bang - Bang Terhadap Kekerasan Komunikasi Verbal Pe serta Didik SMK Al Ikhlas Losari Kabupaten Brebes - Elkhasani, Moh (Indonesian Journal Publisher, 2026)
This study examines the growing interaction in online gaming, particularly Mobile Legends: Bang Bang, which potentially triggers verbal communication violence among students. The objective of this research is to analyze the effect of playing intensity of Mobile Legends on the tendency of verbal communication violence among students of SMK Al Ikhlas Losari, Brebes Regency. This study uses a quantitative survey approach involving 66 respondents selected through purposive sampling from a population of 192 students. Data were collected through questionnaires, interviews, and documentation, then analyzed using simple linear regression. The results show that playing Mobile Legends has a positive and significant effect on verbal communication violence, with a significance value of 0.000 (<0.05) and a coefficient of determination of 22.3%. This indicates that gaming intensity contributes to increased aggressive communication behavior, although the majority of influencing factors lie outside the scope of this study. The contribution of this research lies in providing empirical evidence regarding the relationship between online gaming activities and adolescent verbal communication behavior, which can serve as a foundation for developing digital literacy education and behavioral control strategies in school environments.